Drug-induced gingival enlargement - Part II. Antiepileptic drugs: not only phenytoin is involved - Lin,Katia (2007)
INTRODUCTION: Gingival enlargement is the term now used to describe medication-related gingival overgrowth or gingival hyperplasia, a common reactionary phenomenon that occurs with the use of several types of therapeutic agents, including antiepileptic drugs. This disorder has been recognized since 1939, shortly after the introduction of phenytoin. METHODS: Review of literature concerning etiology, pathogenesis and management of antiepileptic drug induced gingival enlargement. CONCLUSIONS: It is important that neurologists become aware of the potential etiologic agents of antiepileptic drug induced gingival enlargement and its characteristic features in order to be able to prevent, diagnose and successfully manage it.